Training Volume and Intensity of Physical Activity among Young Athletes: The Health Promoting Sports Club (HPSC) Study - Aira Tuula; Salin Kasper; Vasankari Tommi; Korpelainen Raija; Parkkari Jari; Heinonen Olli J; Savonen Kai; Alanko Lauri; Kannas Lasse; Selänne Harri; Villberg Jari; Vähä-Ypyä Henri; et al. (Scientific Research, 2025)
Both training volume and overall physical activity (PA) play a role in young athletes’ sports performance and athletic development. The purpose of this study was to describe the training volume and PA of young athletes in endurance, aesthetics, ball games, and power sports. Questionnaire data (n = 671) were obtained from 15-year-old Finnish athletes on sports participation, along with accelerometer data (n = 350) assessing the amount and intensity of their PA. The athletes’ mean weekly training volume was 11 h 41 min. Objectively assessed PA amounted to 4 h 31 min daily, out of which 1 h 31 min was at a level of moderate-to-vigorous intensity (MVPA). Among 24% of the athletes, the weekly training volume (in hours) exceeded the recommended level of age-in-years, which might increase their risk of sports injuries. At the same time, one in six athletes (16%) did not—on average—reach the internationally recommended threshold level of at least 60 minutes of MVPA per day. Compared to girls, boys averaged 2.5 more hours of training per week, and had 21 more minutes of MVPA per day. Moreover, boys had a higher goal orientation than girls, with 52% of the boys and only 29% of the girls focused on success at adult level. Although total training volume and PA did not differ among sports types, there were differences in training forms, and in the proportions of MVPA. The young athletes were found to vary greatly in training forms, training volumes, MVPA, and goal orientation; hence, training should be planned individually, both for team sports and individual sports.